A Unique Case of Pneumatised Styloid Process with Cholesteatoma. (4th June 2013) - Alam, Mostayn; Dwivedi, Raghav C.; Riffat, Faruque; Scoffings, Daniel; Moffat, David; Jani, Piyush
Abstract : Pneumatisation of styloid process is a very rare finding and has never been reported previously. We present a unique case of a pneumatised styloid process with a cholesteatoma arising within the cavity. We describe the clinical features, associated radiological findings, and management of this lesion.